The level of knowledge and skills in the use of information and communication technology (ICT) among hospital department lecturers in selected vocational colleges in Sabah and Sarawak - Abd Wahab, Nabila; Zakaria, Anis (Dictorate of Journal Publication, 2023)
Along with the current modernization and technology is developing rapidly in all corners making technology an essential medium in human life. In discussing this aspect, the development of technology has brought changes to various sectors, especially in the world of education. Technology makes the world of education experience a change in the learning paradigm, such as the learning process can be done through an online application system, learning methods used in the concept of applications using the internet and various other facilities. Technology also makes the learning process easier and more flexible. Nevertheless, it still annoys the parties involved in monitoring the student's movement and level of understanding. This study was conducted in several Vocational Colleges in Sabah and Sarawak. They involve 117 lecturers at Tawau, Keningau, Bintulu, Sibu and Matang Vocational Colleges. The sample selection is made by selecting lecturers in the snowball method. The study's findings show lecturers' knowledge level about ICT with a mean of 4.12 (SP=0.41). Skills in Information and Communication Technology (ICT) also got a high score with a mean of 3.80 (SP=0.52). In the correlation findings of this study, there is a significant relationship between the level of knowledge and the skill of using ICT in learning. In this regard, teachers, especially in this discussion with Vocational College lecturers and parents, play a significant role in monitoring the children so that the learning concept of this technology can be used in the best way and provide continuous facilities like learning in the classroom. It should be noted that the level of student understanding depends on each individual. Therefore, in assessing the successful use of this strategy in educational institutions, efforts to help teachers improve their competence in online learning can be made through the training and mentoring process.